The fragmentation degree of forest cover in the Fitogeografic Units (FU) of Costa Rica was studied during three years: 1997, 2000 and 2005. - Calvo-Obando, Ana (2012)
This permitted to calculate the annual percentage change rate using the formula proposed by Puyravaud (2003). Software that allows both vectorial and raster formats was used, such as: ArcView 3.3, ArcGis 9.3 and FRAGSTATS 3.3. The measurements of fragmentation calculated by software FRAGSTATS 3.3 were: remnant area, number of patches (NP), mean nearest neighbor distance (MNN) and patch density (PD). During the period 1997-2000 9 139 hectares were deforested, 54,8% was concentrated in the UF 3a (Tortuguero plains, lowlands), while in the period 2000-2005, 23 699 hectares were cut, of which 18,6% was concentrated in the UF 3a (Tortuguero plains, lowlands), nevertheless it appeared recovery of forest cover. Only during the period 2000-2005 were identified processes of loss and recovery of forest cover simultaneously.